Effect of dexamethasone in postoperative pain in endodontics: integrative literature review (Research, Society and Development, 2023)
A frequent problem in Endodontics is post-operative pain, which can vary from a low-intensity sensitivity when biting on the tooth, to severe pain with a light touch. The development of postoperative pain in endodontics is usually caused by an inflammatory response in the periapical tissues. There are drugs that control the synthesis of inflammatory mediators, such as dexamethasone, which should be considered for prevention in controlling the inflammatory reaction, and thus preventing pain after endodontic treatment. The objective of this work was to carry out an integrative review of the current literature on the use and efficacy of dexamethasone in endodontics. It was carried out through a search for scientific articles in the PubMed electronic database using the descriptors: dexamethasone endodontics, efficacy dexamethasone endodontics, indexed from 2012 to February 2021, involving clinical trials. Eight articles fully published in English met the eligibility criteria. The selected studies showed that the use of dexamethasone administered orally or by intraligamentary injections as premedication, during procedures or postoperatively is effective in controlling pain after endodontic procedures.